Magnitude of Enterococcal Bacteremia in Trauma Patients Admitted for Intensive Trauma Care: A Tertiary Care Experience from South Asian Country - Rajkumari, Nonika; Mathur, Purva; Thanbuana, Bariamtak; Sajan, Swaminathan; Misra, Mahesh C (Journal of Laboratory Physicians, 2015)
Background: Bloodstream infection (BSI) and bacteremias due to Enterococcus spp. are increasing worldwide with the current need to understand its causes among hospitalized trauma patients. Hence, the study was conducted.Methodology: A 3-year retrospective laboratory cum clinical based study was performed at a level I trauma center in India. Patients with health care associated enterococcal bacteremia were identified using the hospital database, their episodes of BSI/bacteremia calculated and their clinical records and treatment were noted.Results: A total of 104 nonrepetitive Enterococcus spp. was isolated of which Enterococcus faecium was the most common (52%). High-level resistance to gentamicin high-level aminoglycoside resistance was seen in all the Enterococcus spp. causing bacteremia, whereas a low resistance to vancomycin and teichoplanin was observed. Overall mortality was more in patients infected with vancomycin-resistant Enterococcus (5/11, 46%) compared to those with vancomycin sensitive Enterococcus (9/93, 10%); though no significant association of mortality with Enterococcus spp. bacteremia (P > 0.05) was seen. The rate of bacteremia due to Enterococcus spp. was 25.4 episodes/1,000 admissions (104/4,094) during the study period.Conclusion: Enterococcal bacteremia is much prevalent in trauma care facilities. Here, a microbiologist can act as a sentinel and help in preventing such infections.
Keywords: Bacteremia; drug resistance; Enterococcus sp.; trauma; vancomycin-resistant Enterococcus